2015
DOI: 10.1007/s10151-015-1270-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of analgesic modality on stress response following laparoscopic colorectal surgery: a post-hoc analysis of a randomised controlled trial

Abstract: There is a significant transient attenuating effect of TEA on stress response following laparoscopic colorectal surgery and within ERAS as expressed by serum epinephrine and insulin levels. Continuous wound infusion with local anaesthetic, however, attenuates cytokine response as expressed by interleukin-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“… compared preperitoneal CWI with epidural analgesia and reported excellent analgesic efficacy in the CWI group with no difference in hospital stay between the two groups. The same investigators showed that pain and opiate consumption during the two postoperative days after laparoscopic colorectal resections did not differ between the epidural and CWI groups . Several parameters could explain the discrepancies between these results, such as the catheter location (preperitoneal vs subcutaneous) and local anaesthetic flow rates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… compared preperitoneal CWI with epidural analgesia and reported excellent analgesic efficacy in the CWI group with no difference in hospital stay between the two groups. The same investigators showed that pain and opiate consumption during the two postoperative days after laparoscopic colorectal resections did not differ between the epidural and CWI groups . Several parameters could explain the discrepancies between these results, such as the catheter location (preperitoneal vs subcutaneous) and local anaesthetic flow rates.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, according to some recent reports, it is thought that an analgesic strategy may influence the stress response after laparoscopic colorectal surgery . Stress response corresponds to the initiation of a cascade of neuroendocrine, metabolic and inflammatory responses induced by the surgical injury.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies in the present meta-analysis are randomised and in all studies [712] the random sequence generation and allocation concealment were reported and were unclear just in one study, giving strength to the results of the meta-analysis. However, although blinding is very important when evaluating pain control, only the study by Boulind et al [10] was blind.…”
Section: Discussionmentioning
confidence: 99%
“…Using spinal or epidural anaesthesia reduce hormonal stress [46,47]. (table IV), but this sub-study was neither aimed nor designed or powered to investigate any correlation.…”
Section: Limitationsmentioning
confidence: 99%